A History of Violence: Field Evidence on Trauma, Discounting and Present Bias - Alex Imas; Michael A. Kuhn; Vera Mironova (Center for Economic Studies and ifo Institute (CESifo), 2015)
The extent to which individuals discount the future and whether they discount in a time-consistent fashion is an important determinant of their life outcomes. Using a field experiment in the Democratic Republic of Congo, we show that direct exposure to violence substantially increases present bias – choice of the smaller, immediate reward over the larger, later reward. We demonstrate that providing individuals with a delay between information about the choice and the choice itself mitigates the differences in behavior between those who were exposed to violence and those who were not. Our findings suggest that enforcing a cooling off period between income notification and consumption opportunities may help generate more patient choices and mitigate the elevated impulsivity of individuals that have experienced violence. We measure our treatment effects both in reduced-form as well as in the form of structural estimates of a quasi-hyperbolic discounting function to enable comparison with measures of other types of time inconsistency and a welfare evaluation of the treatment effect. Our results have implications for policies aimed at alleviating the deleterious effects of present bias and the role of deliberation in the structure of commitment contracts.
Keywords: C93; D14; F51; 330; present bias; violence; field experiments